LO65: Frailty and associated outcomes among emergency department patients requiring endotracheal intubation. (May 2019) - Fernando, S.; McIsaac, D.; Rochwerg, B.; Bagshaw, S.; Seely, A.; Perry, J.; Dave, C.; Tanuseputro, P.; Kyeremanteng, K.
Abstract : Introduction : Risk-stratification of patients requiring endotracheal intubation and mechanical ventilation in the Emergency Department (ED) is necessary for informed discussions with patients regarding goals-of-care. Frailty is a clinical state characterized by reduced physiologic reserve, and resulting from accumulation of physiological stresses and comorbid disease. Frailty is increasingly being identified as an important independent predictor of outcome among critically ill patients. Our objective was to identify the impact of clinical frailty (defined by the Clinical Frailty Scale [CFS]) on in-hospital mortality and resource utilization of ED patients requiring endotracheal intubation and mechanical ventilation.Methods : We analyzed a prospectively collected registry (2011-2016) of patients requiring endotracheal intubation in the ED at two academic hospitals and six community hospitals. We included all patients ≥18 years of age, who survived to the point of ICU admission. All patient information, outcomes, and resource utilization were stored in the registry. CFS scores were obtained through chart abstraction by two blinded reviewers. The primary outcome, in-hospital mortality, was analyzed using a multivariable logistic regression model, controlling for confounding variables (including patient sex, comorbidities, and illness severity). We defined "frailty" as a CFS ≥ 5.Results : 4, 622 patients were included. Mean age was 61.2 years (SD: 17.5), and 2, 614 (56.6%) were male. Frailty was associated with increased risk of in-hospital mortality, as compared to those who were not frail (adjusted odds ratio [OR] 2.21 [1.98-2.51]). Frailty was also associated with higher likelihood of discharge to long-term care (adjusted OR 1.78 [1.56-2.01]) among patients initially from a home setting. Frail patients were more likely to fail extubation during their hospitalization (adjusted OR 1.81 [1.67-1.95]) and were more likely to require tracheostomy (adjusted OR 1.41 [1.34-1.49]).Conclusion : Presence of frailty among ED patients requiring endotracheal intubation and mechanical ventilation was associated with increased in-hospital mortality, discharge to long-term care, extubation failure, and tracheostomy. ED physicians should consider the impact of frailty on patient outcomes, and discuss associated prognosis with patients prior to intubation.